Psychological maintenance as an integrated approach to prevention and correction of professional burning out of the medical staff - Kucher, V. S.; Vodopyanova, N. E. (Uchenye zapiski (Sankt-Peterburgskiĭ gosudarstvennyĭ medit͡s︡inskiĭ universitet im. akad. I.P. Pavlova), 2014)
The syndrome of professional burning out is a complex of symptoms and signs evidenced in various negative psychic conditions at individual, interpersonal and organizational levels. It is formed owing to a long mismatch between the requirements of the professional environment and the resources of the expert. Analysis of the preventive and correctional programs as a psychological assistance showed insufficiency of such approach. Creation of preventive and correctional programs within psychological maintenance from the position of involution of professional resources, taking into account the theoretical - methodological basis (the concept, the purposes, tasks, system approach, criteria of efficiency) and the subjective-personal resources of counteraction directed at activization to burning out at all stages of professional development is progressive.